Specific mutations in the C-terminus domain of HBV surface antigen significantly correlate with low level of serum HBV-DNA in patients with chronic HBV infection. Issue 3 (March 2015) - Mirabelli, Carmen; Surdo, Matteo; Van Hemert, Formijn; Lian, Zhichao; Salpini, Romina; Cento, Valeria; Cortese, Maria Francesca; Aragri, Marianna; Pollicita, Michela; Alteri, Claudia; Bertoli, Ada; Berkhout, Ben; et al.
Summary: Background: To define HBsAg-mutations correlated with different serum HBV-DNA levels in HBV chronically-infected drug-naive patients. Methods: This study included 187 patients stratified into the following ranges of serum HBV-DNA:12–2000 IU/ml, 2000–100, 000 IU/ml, and >100, 000 IU/ml. HBsAg-mutations were associated with HBV-DNA levels by applying a Bayesian-Partitional-Model and Fisher-exact test. Mutant and wild-type HBV genotype-D genomes were expressed in Huh7 cells and HBsAg-production was determined in cell-supernatants at 3 days-post-transfection. Results: Specific HBsAg-mutations (M197T, -S204N-Y206C/H-F220L) were significantly correlated with serum HBV-DNA <2000 IU/ml (posterior-probability>90%, P  < 0.05). The presence of Y206C/H and/or F220L was also associated with lower median (IQR) HBsAg-levels and lower median (IQR) transaminases (for HBsAg:250[115–840] IU/ml for Y206C/H and/or F220L versus 4300[640–11, 838] IU/ml for wild-type, P  = 0.023; for ALT:28[21–40] IU/ml versus 53[34–90] IU/ml, P  < 0.001). These mutations were localized in the HBsAg C-terminus, known to be involved in virion and/or HBsAg secretion. The co-occurrence of Y206C + F220L was found significant by cluster-analysis, ( P  = 0.02). In addition, in an in-vitro model Y206C + F220L determined a 2.8–3.3 fold-reduction of HBsAg-amount released in supernatants compared to single mutants and wt (Y206C + F220L = 5, 679 IU/ml; Y206H = 16, 305 IU/ml; F220L = 18, 368 IU/ml; Y206C = 18, 680 IU/ml; wt = 14, 280 IU/ml, P  < 0.05). Conclusions: Specific HBsAg-mutations (compartmentalized in the HBsAg C-terminus) correlated with low-serum HBV-DNA and HBsAg-levels. These findings can be important to understand mechanisms underlying low HBV replicative potential including the inactive-carrier state. Highlights: An integrative approach of sequence analyses, mathematical models and phenotypic assays was used in this work. Novel HBsAg-genetic markers correlated with different levels of serum HBV-DNA in HBV chronically-infected patients. Mutations compartmentalized at the C-terminus of the HBsAg correlated with HBV-DNA ≤2, 000 UI/ml and low HBsAg titer. The impact of such markers on the release of HBsAg has been validated with an in vitro model.